ANALISIS MANAJEMEN SARANA DAN PRASARANA DI SMP PANCA BUDI MEDAN - Irvan Malay; Indra Benny Sitorus; M. Rafli Zain; Serly Serly; Sugianto Sugianto; Syahrial Hasanuddin Pohan (Universitas Islam Sumatera Utara, 2025)
Inadequate infrastructure and facilities can have a detrimental effect on teacher effectiveness and student learning motivation. Therefore, schools need to have a structured and sustainable facilities and infrastructure management system. In this case, the school should continuously analyse the facilities and infrastructure management system that has been implemented at SMP Panca Budi Medan and identify areas that need improvement. In this research, the author uses Qualitative Research Method by using observation approach and conducting direct interview with the Principal to find out information about facilities and infrastructure in SMP Panca Budi.The instrument used in this research is using observation sheet which consists of four aspects, namely: Based on the results of observations carried out at SMP Panca Budi Medan, there are several things that can be concluded, namely: the availability of facilities and infrastructure in the school is complete; the condition of the available facilities is good after comparing the availability and ideal needs; the condition of the available infrastructure is good, although there is one aspect that needs to be added, namely toilets; and that SMP Panca Budi Medan already has inventory documents and long-term development planning so that it will facilitate school development.